On improvements of Double Beta Decay using FQTDA Model - Oliveira, L. de (2015)
The Quasiparticle Tamm-Dancoff Approximation (QTDA) is applied to describe the nuclear double beta decay with two neutrinos. Several serious inconveniences found in the Quasiparticle Random Phase Approximation (QRPA) are not present in the QTDA, as such as the ambiguity in treating the intermediary states, and further approximations necessary for evaluation of the nuclear matrix elements (NMEs) or, the extreme sensitivity of NME with the ratio between the pn and pp + nn pairings. Some years ago, the decay 48Ca → 48Ti was discussed within the particle-hole limit of QTDA. We found some mismatch in the numerical calculations when the full QTDA was being implemented, and a new performance in the particle-hole limit of QTDA is required to guarantee the fidelity of the approximation.